Forked Fungus Beetle (suggested common name) Bolitotherus cornutus (Panzer) 1794 (Insecta: Coleoptera: Tenebrionidae) - Ummat Somjee; Andrea Lucky (EDIS)
The forked fungus beetle, Bolitotherus cornutus (Panzer), is a cryptic horned beetle in the family Tenebrionidae that is found throughout much of eastern North America. The most distinctive feature of the forked fungus beetle is a pair of forward-facing horns that emerge from the thorax of the adult male (Figure 1). Males use these horns in competitions with rivals for access to reproductive opportunities with females. These beetles spend most of their lives on or within shelf fungi that grow on decaying logs. The fascinating life history of the forked fungus beetle makes this insect an excellent model for studying behavior, population dynamics, and sexual selection.